Pengaruh Profitabilitas Dan Kepemilikan Manajerial Terhadap Kebijakan Dividen Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Arista Pradnyani, I Gusti Agung; Pramita Indraswari, I Gusti Agung Ayu; Nila Rahayu (Universitas PGRI Yogyakarta, 2024)
This research aims to analyze the influence of profitability and managerial ownership on dividend policy, with company size as a moderating variable. Research was conducted on banking sector companies on the IDX for the 2018-2021 period. The sample was determined using a purposive sampling technique, with the sample in this study totaling 32. The results of the study concluded that profitability has a positive influence on dividend policy, while managerial ownership has a negative influence on dividend policy. Company size is proven to moderate the relationship between profitability and dividend policy, as well as weakening the relationship between managerial ownership and dividend policy.